Direction of trade statistics yearbook 1997 - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This twenty-sixth yearbook issue of Direction of Trade Statistics (DOTS) presents, for 161 countries, figures on the value of merchandise exports and imports by trade partners for the years 1984 through 1990, as well as area and world aggregates showing trade flows between major areas of the world.
sju 11/03/2020
Ref
Keywords: International trade; Commercial statistics